1985
DOI: 10.1007/bf00143213
|View full text |Cite
|
Sign up to set email alerts
|

Pattern electroretinograms recorded with a skin electrode in pigmentary retinal degeneration

Abstract: In 24 patients suffering from pigmentary retinal degeneration the electroretinograms to pattern stimulation (PERG) were recorded with a silver-cup electrode placed on the center of the lower eyelid skin referred to an electrode on the earlobe. The results were compared with the responses to flash stimulation (FERG) and pattern visual evoked cortical potentials. None of patients showed normal FERGs. Nineteen of 48 eyes showed subnormal FERGs. The PERG was recorded from those 19 eyes. In the remaining 29 eyes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Our previous studies [1][2][3] on patients with RP showed a good correlation between visual acuity, central visual field, and PVECPs in observations of [8], sensitivity drops at lower frequencies in curves obtained with homogeneous field stimuli [9,10], while no attenuation occurs with spatially structured stimuli. Using PVECPs to checkerboard stimuli, we found slightly low frequency attenuation in normal human subjects [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies [1][2][3] on patients with RP showed a good correlation between visual acuity, central visual field, and PVECPs in observations of [8], sensitivity drops at lower frequencies in curves obtained with homogeneous field stimuli [9,10], while no attenuation occurs with spatially structured stimuli. Using PVECPs to checkerboard stimuli, we found slightly low frequency attenuation in normal human subjects [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…A more ideal procedure is the visual evoked cortical potential to pattern stimuli (PVECP) because it reveals central visual function without requiring bright light adapation. We have, therefore, been studying [1][2][3] the application of PVECP to patients with RP.…”
Section: Introductionmentioning
confidence: 99%